2021
DOI: 10.1111/bjh.17740
|View full text |Cite
|
Sign up to set email alerts
|

The real impact of COVID‐19 on an East London Sickle cell population: results of a service‐wide survey

Abstract: Fig 1. Distribution of answers according to genotype (A), age (B) and gender (C). Vaccination Y/NY, vaccinated already/keen to be vaccinated but not yet received first dose; Vaccination U, uncertain whether to be vaccinated; Vaccination DW, does not want to be vaccinated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…16 However, a study of a population of patients with SCD in London found that vaccination uptake was around 80%, higher than among older people of African origin in general. 17 These safety results for COVID-19 vaccines are reassuring and might help to promote vaccination among reluctant patients at a high risk of COVID-19.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…16 However, a study of a population of patients with SCD in London found that vaccination uptake was around 80%, higher than among older people of African origin in general. 17 These safety results for COVID-19 vaccines are reassuring and might help to promote vaccination among reluctant patients at a high risk of COVID-19.…”
Section: Discussionmentioning
confidence: 90%
“…Studies in many countries have shown that the socio‐professional category, ethnicity, geographical origin and political affiliations can influence the level of vaccination 16 . However, a study of a population of patients with SCD in London found that vaccination uptake was around 80%, higher than among older people of African origin in general 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some studies suggest that when it comes to COVID-19, individuals with sickle cell disease or sickle cell trait have similar rates of death, hospitalization, and ICU admission compared to people without sickle cell disease or sickle cell trait ( 31 , 34 , 42 , 47 , 49 , 58 , 70 , 80 , 85 , 87 , 108 ). These papers did not identify mechanisms related to sickle cell disease that act directly in the clinical course of COVID-19 but instead highlighted features also observed in the general population, such as the existence of other comorbidities, advanced age, and the presence of organ damage, as risk factors for unfavorable outcomes ( 57 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination, an essential tool for reducing mortality from infectious causes in this population, should also be encouraged in all age groups, as it has been for the general population ( 2 , 47 , 106 ). Studies show that there may be some hesitation among people with sickle cell disease regarding the safety profile of immunizers against SARS-CoV-2 and the occurrence of adverse effects ( 121 ).…”
Section: Discussionmentioning
confidence: 99%